ZIF-8 derived Fe‒N coordination moieties anchored carbon nanocubes for efficient peroxymonosulfate activation via non-radical pathways: Role of FeNx sites - He, Jingjing; Wan, Yu; Zhou, Wenjun (Journal of hazardous materials, 2021)
Developing high-efficient hybrids carbon catalysts for PMS-based advanced oxidation process (AOPs) are crucial in the field of environmental remediation. In this work, novel carbon nanocubes (xFe‒N‒C) with three-dimensional porous structure and abundant well-dispersed FeNx sites were obtained via a skillful cage-encapsulated-precursor pyrolysis strategy. The as-synthesized xFe‒N‒C exhibited superb activity for phenol degradation by activating peroxymonosulfate (PMS). Besides, the catalytic system not only possessed good recycling performance, wide pH adaptation and relatively low activation energy, but also had high resistance to environmental interference. Singlet oxygen (1O2) dominated non-radical process was responsible for phenol degradation rather than traditional radical pathways. Impressively, the doping level of Fe could regulate FeNx contents in catalysts, and the catalytic activity of xFe‒N‒C was greatly enhanced with increasing FeNx contents. Based on density functional theory calculations (DFT), the introduction of FeNx sites regulated the electronic structure of catalysts. Such electron-deficient Fe center acted as electron acceptor to receive electrons transmitted by the adsorbed PMS, thus generating highly reactive 1O2 for rapid phenol oxidation. This work provides a new insight into the innovation in transition metal-nitrogen hybrid carbon catalysts and highlights the pivotal roles of FeNx sites in 1O2 generation during PMS activation process. [Display omitted] •Carbon nanocubes with abundant FeNx active sites were successfully synthesized.•Fe‒N‒C exhibited excellent catalytic activity and stability.•Fe‒N‒C/PMS system possessed high tolerance to pH and water constituents.•The crucial role of FeNx sites in carbocatalysis was revealed by DFT calculations.•Dominant 1O2 was identified and PMS activation mechanism was elucidated.